Genre of Students’ Descriptive Text: A Case of Texts Developed by Tenth Grade Students of SMA Teuku Umar Semarang - Ulya, Himatul; Widhiyanto, Widhiyanto (Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates the genre analysis of descriptive texts written by tenth-grade students at SMA Teuku Umar Semarang. It examines students’ mastery of generic structures and linguistic features, focusing on identification, description, present tense, adjectives, and relational verbs also it strengths and weaknesses. Using a qualitative descriptive design, data were collected from 25 students and analyzed through the genre framework of Tardy and Swales (2021). Findings show that most students applied the generic structures correctly, though the level of descriptive detail varied from minimal to fairly elaborate. Linguistic features were generally appropriate, but limited vocabulary and frequent mechanical errors persisted, reducing accuracy and coherence. The study concludes that while structural mastery has been achieved, linguistic sophistication remains a challenge, highlighting the need for pedagogical strategies that integrate genre-based scaffolding with explicit language development.